Full-Thickness Scar Resection After R1/Rx Excised T1 Colorectal Cancers as an Alternative to Completion Surgery. (31st December 2021) - Gijsbers, Kim M.; Laclé, Miangela M.; Elias, Sjoerd G.; Backes, Yara; Bosman, Joukje H.; van Berkel, Annemarie M.; Boersma, Femke; Boonstra, Jurjen J.; Bos, Philip R.; Dekker, Patty A.T.; Didden, Paul D.; Geesing, Joost M.J.; et al.
Abstract : INTRODUCTION: Local full-thickness resections of the scar (FTRS) after local excision of a T1 colorectal cancer (CRC) with uncertain resection margins is proposed as an alternative strategy to completion surgery (CS), provided that no local intramural residual cancer (LIRC) is found. However, a comparison on long-term oncological outcome between both strategies is missing. METHODS: A large cohort of patients with consecutive T1 CRC between 2000 and 2017 was used. Patients were selected if they underwent a macroscopically complete local excision of a T1 CRC but positive or unassessable (R1/Rx) resection margins at histology and without lymphovascular invasion or poor differentiation. Patients treated with CS or FTRS were compared on the presence of CRC recurrence, a 5-year overall survival, disease-free survival, and metastasis-free survival. RESULTS: Of 3, 697 patients with a T1 CRC, 434 met the inclusion criteria (mean age 66 years, 61% men). Three hundred thirty-four patients underwent CS, and 100 patients underwent FTRS. The median follow-up period was 64 months. CRC recurrence was seen in 7 patients who underwent CS (2.2%, 95% CI 0.9%–4.6%) and in 8 patients who underwent FTRS (9.0%, 95% CI 3.9%–17.7%). Disease-free survival was lower in FTRS strategy (96.8% vs 89.9%, P = 0.019), but 5 of the 8 FTRS recurrences could be treated with salvage surgery. The metastasis-free survival (CS 96.8% vs FTRS 92.1%, P = 0.10) and overall survival (CS 95.6% vs FTRS 94.4%, P = 0.55) did not differ significantly between both strategies. DISCUSSION: FTRS after local excision of a T1 CRC with R1/Rx resection margins as a sole risk factor, followed by surveillance and salvage surgery in case of CRC recurrence, could be a valid alternative strategy to CS.